PENGARUH MODEL PEMBLAJARAN PROJECT BASED LEARNING BERBANTUAN MIND MAPPING TERHADAP HASIL BELAJAR IPA KELAS V SD ISLAM DARUSSALAM - Rizka; Istiningsih, Siti; Novitasari, Setiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem that is often found in learning is the low learning outcomes of students. One of the factors is the application of ineffective and innovative learning models. Based on the results of observations, it was found that the learning outcomes of class V students at SD Islam Darussalam in science subjects were relatively low, namely around 70% of students had not yet reached the KKM. This research aims to determine the effect of the Project based learning model assisted by mind mapping on the science learning outcomes of Class V at SD Islam Darussalam. The type of research used is quantitative research with a pre-experimental method, one group pretest posttest design. Sampling in this study used a non-probability sampling technique with a saturated sample type, namely all students in class V of SD Islam Darussalam, totaling 32 students. Data collection uses observation, test and documentation techniques. Based on the results of research using the Paired samples T-Test statistical test, it was found that significance (Two Side P) was >0.001, smaller than 0.05, so Ha was accepted. So it can be concluded that the Project based learning model assisted by mind mapping has an influence on the science learning outcomes for class V at SD Islam Darussalam.